Pertumbuhan dan Biomassa Albizia saponaria yang Diinokulasi Fungi Arbuskula Mikoriza Lokal Sulawesi Tenggara - Faisal Danu Tuheteru; Husna Husna (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2011)
The study of effect of local AMF species from Southeast Sulawesi on A. saponaria was not yet conducted. The aim of this research was to know the effectiveness of local AMF species. A completely randomized design with three replications -1 was used in this research. The treatments tried were no inoculation of AMF (A), inoculated with AMF inoculum 10 g. polybag (B), and 20 g. -1 polybag (C). The seedling parameters observed were height, diameter, number of leaves, shoot biomass, root biomass, total biomass, number of nodule and percentage of root colonization. Result of the research showed that the application of AMF inoculum 10 g.-1 polybag (B) 20 g.-1 and polybag (C) tended to give the best effect on increasing all of the parameters observed compared of control treatment.